Empowering Women through Microfinance: A Case Study of Jalpa Samudayik Laghubitta Bittya Sanstha Ltd. in Pokhara Metropolitan City - Dhungana, Bharat Ram; Ranabhat, Deepesh; Ojha, Deepak; Lamichhane, Keshav; Acharya, Sujana; Subedi, Sadiksha (Saptagandaki Journal, 2023)
Empowering women is crucial for global development and promoting gender equality. Microfinance plays a vital role in women's empowerment. This study investigated the impact of microfinance services on women’s empowerment in Pokhara Metropolitan City, specifically focusing on Jalpa Samudayik Laghubitta Bittya Sanstha Limited (JALPA). The research involved 152 female clients in Pokhara, using a structured questionnaire for primary data collection. Data were analysed using both descriptive and inferential statistics. The study revealed significant positive changes in economic empowerment, including enhanced access to microcredit, property ownership, job opportunities, health services, and life insurance schemes. Moreover, improvements were observed in socio-political empowerment, reflected in increased participation in social, political, and religious organizations, leadership roles, and the ability to express opinions in public. The findings also highlighted positive transformations in decision-making power, respect, communication, confidence, and access to training opportunities after joining microfinance institutions (MFIs). This study concludes that microfinance interventions play a pivotal role in positively influencing women's economic status, decision-making capabilities, and socio-political involvement. The study not only provides empirical evidence but also emphasizes the need for improvements in the design of microfinance programs to comprehensively address the diverse dimensions of women's empowerment.